تشييء المرأة في الرواية العربية - السامرائي أ.م.د. سهام حسن جواد (Aljameai, 2022)
الملخص: الرواية في عالم اليوم تحولت إلى تعبيرٍ حياتي متطورٍ ومتجددٍ، فهي تسهم في تصوير واقع الإنسان اليومي، وممارساته مع نفسه، ومع المجتمع. وسيلة مُثلى لتقديم صورة مجتمعٍ ما لدى مجتمعاتٍ أخرى فهي تمثّل الواقع المعاش على اختلاف الثقافات. فضلاً عن أنَّها تسهم بشكلٍ كبيرٍ في تشكيل ثقافتنا، ونظرتنا للأشياء. وربما تحمل نسقًا ثقافيًا، يرتبط بالإشكالات السياسية، والاجتماعية المتزامنة معها. وحرصت الرواية على إبقاء المرأة في حساباتها؛ بل إقحامها أحيانًا في مشاهد ساخنةٍ من دون ضرورةٍ؛ لدغدغة نهم القارئ الباحث عن المرأة في الرواية، فبات من المألوف وجود مشاهد إغراءٍ حتى لو كانت القصة لا تستدعي وجود هذه المشاهد كوسيلة ترويجٍ على النحو الذي يوحي أنَّ الروائي كأنَّه يقول: اقرأ الرواية، وفز بمشهدٍ مجاني لامرأةٍ عابرةٍ. والرواية التي تقدّم المرأة بهذا الشكل فإنَّها تسهم في استغلال، وإساءة، وتشويه، وتجريد إنسانيتها فضلاً عن أنَّها تسهم في غرس أفكار، وقيم، ومثل تغيّر البنية الفكرية للمجتمع، مفاهيم لا ترى في المرأة سوى جسدًا جميلاً مغريًا، يتمّ عرضه؛ لإعطاء المتلقي جوًا من الإثارة والمتعة. كإغراءٍ لشدّ الانتباه، وبذلك تعزز صورةً ثابتةً. في ضوء هذا الأفق اشتغلت هذه الورقة على مناقشة ظاهرة تشييء المرأة في الرواية العربية - رواية عزا زيل ليوسف زيدان أنموذجًا . مادة البحث أوجبت أن أتكلم أولاً عن مفهوم التشييء لغةً واصطلاحًا ، وذكر أهم آراء الفلاسفة وعلماء النفس والاجتماع في مفهوم التشييء والحديث عن أهمية الرواية في عالم اليوم قبل الدخول في الجانب التطبيقي للدراسة . Abstract : In today’s world, the novel has turned into an evolving and renewed life expression, as it contributes to portraying the daily reality of man, and his practices with himself and with society. An ideal way to present the image of one society to other societies, as it represents the lived reality in different cultures. In addition, it contributes greatly to shaping our culture and our view of things. And perhaps it bears a cultural pattern, related to the political and social problems concurrent with it. The novel was keen to keep the woman in its interest; sometimes even unnecessarily inserting her into hot scenes; To tickle the insatiable reader who is looking for women in the novel, it has become common for tempting scenes to exist, even if the story does not call for the presence of these scenes as a means of promotion. The novel, which presents women in this way, contributes to the exploitation, abuse, distortion, and dehumanization of her, as well as the instillation of ideas, values, and such as changing the intellectual structure of society, concepts that do not see in women anything but a beautiful and seductive body, which is presented; To give the recipient an atmosphere of excitement and fun. As a lure to grab attention, thereby enhancing a stable image. In the light of this horizon, this paper worked on discussing the phenomenon of women’s objectification in the Arab novel - the novel attributed to Youssef Zeidan as a model. The research subject necessitated that I first talk about the concept of objectification linguistically and idiomatically. in addition to mention the most important views of philosophers, psychologists and sociologists in the concept of objectification and talk about the importance of the novel in today’s world before entering into the applied side of the study.